An Oral Health Study of Centenarians and Children of Centenarians. Issue 6 (2nd June 2014) - Kaufman, Laura B.; Setiono, Tiffany K.; Doros, Gheorghe; Andersen, Stacy; Silliman, Rebecca A.; Friedman, Paula K.; Perls, Thomas T.
<x xml:space="preserve">Abstract</x> Objectives To determine whether oral health is better in centenarians than in a published birth cohort–matched sample and to compare oral health in centenarian offspring with a case‐controlled reference sample. Design Observational cross‐sectional study. Setting New England Centenarian Study (NECS). Participants Seventy‐three centenarians, 467 offspring, and 251 offspring generation‐reference cohort subjects from the NECS. Measurements A self‐report questionnaire was administered to measure oral health in all three groups, with edentulous rate as the primary outcome measure. The NECS made information on sociodemographic characteristics and medical history available. Centenarian results were compared with published birth cohort–matched results. Data from offspring and reference cohorts were analyzed to determine differences in oral health and associations between oral health measures and specific medical conditions. Results The edentulous rate of centenarians (36.5%) was lower than that of their birth cohort (46%) when they were aged 65 to 74 in 1971 to 1974 (according to National Center of Health Statistics). Adjusting for confounding factors, the reference cohort was more likely to be edentulous (adjusted odds ratio (AOR) = 2.78, 95% confidence interval CI = 1.17–6.56), less likely to have all or more than half of their own teeth (AOR = 0.48, 95% CI = 0.3–0.76), and less likely to report excellent or very good oral health (AOR = 0.65, 95% CI = 0.45–0.94) than the centenarian offspring. Conclusion Centenarians and their offspring have better oral health than their respective birth cohorts. Oral health may prove to be a helpful marker for systemic health and healthy aging.